2017
DOI: 10.1152/ajpheart.00576.2017
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetically-mediated cardiac responses to isolated muscle metaboreflex activation following exercise are modulated by body position in humans

Abstract: Isolated muscle metaboreflex activation with posthandgrip exercise ischemia (PEI) increases sympathetic nerve activity and partially maintains the exercise-induced increase in blood pressure, but a smaller heart rate (HR) response occurs. The cardiopulmonary baroreceptors, mechanically sensitive receptors that respond to changes in central blood volume and pressure, are strongly associated with changes in body position and upon activation elicit reflex sympathoinhibition. Here, we tested the hypothesis that po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…; Teixeira et al. ). Recent studies have established that men have an enhanced sympathetic and pressor response to metaboreflex activation compared to women (Jarvis et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Teixeira et al. ). Recent studies have established that men have an enhanced sympathetic and pressor response to metaboreflex activation compared to women (Jarvis et al.…”
Section: Introductionmentioning
confidence: 99%
“…; Teixeira et al. ). While there are no sex differences in sympathetic baroreflex function in upright posture (Fu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Teixeira et al . ). Human investigations have demonstrated that the return of HR to resting levels is a consequence of cardiac parasympathetic reactivation possibly overcoming the effect of metaboreflex‐induced sympathoexcitation to the heart (Nishiyasu et al .…”
Section: Discussionmentioning
confidence: 97%
“…), and participant body position (Teixeira et al . ). We acknowledge that, because we have only used ischaemic IHG at 30% MVC, care should be taken when extrapolating our findings to the exercise of other muscle groups (i.e.…”
Section: Discussionmentioning
confidence: 97%